1993
DOI: 10.1016/s0022-5347(17)36054-8
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Buccal Mucosa Patch Graft in the Management of Anterior Urethral Strictures

Abstract: We describe our experience with 20 patients undergoing 1-stage correction of an anterior urethral stricture using a buccal mucosa patch graft. This technique was used for treatment of short strictures (1 to 2 cm.) that usually required a 2 to 4 cm. repair, making excision and end-to-end anastomosis impractical. Results were excellent in 18 patients, while 2 required revision for recurrent stricture. Urethrocutaneous fistulas and diverticulas were not encountered in our series. The buccal mucosa patch graft is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(78 citation statements)
references
References 0 publications
2
74
0
2
Order By: Relevance
“…[13] El-Kasaby et al, have described their experience with 20 patients undergoing 1-stage correction of an anterior urethral stricture using a buccal mucosa patch graft; they obtained excellent results in 18 patients. [14] Similarly, Monfort et al, managed strictures in pediatric patients and noted a comparable success rate of 90% for bladder mucosa and oral mucosa. [15] After these initial publications, 1994 onwards several clinical accounts have been published on the use of oral mucosa, especially for small populations of patients.…”
Section: Historical Perspectivementioning
confidence: 94%
“…[13] El-Kasaby et al, have described their experience with 20 patients undergoing 1-stage correction of an anterior urethral stricture using a buccal mucosa patch graft; they obtained excellent results in 18 patients. [14] Similarly, Monfort et al, managed strictures in pediatric patients and noted a comparable success rate of 90% for bladder mucosa and oral mucosa. [15] After these initial publications, 1994 onwards several clinical accounts have been published on the use of oral mucosa, especially for small populations of patients.…”
Section: Historical Perspectivementioning
confidence: 94%
“…Since 1993 ElKasaby et al reported the first experience with buccal mucosa urethroplasty for treatment of penile and bulbar urethral strictures (15), buccal mucosa has become an increasingly popular graft tissue for penile or bulbar urethral reconstruction performed in single or multiple stages because it was readily available in all patients and was easily harvested from the cheek or lip with a concealed donor site scar (16)(17)(18)(19)(20). (21,22).…”
Section: Oral Grafts Urethroplastymentioning
confidence: 99%
“…A padronização da técnica, bem como os resultados preliminares do grupo de Mainz 12 , Alemanha, atraiu o interesse de outros autores [13][14][15] . Dentre as vantagens da mucosa bucal, inclui-se a sua disponibilidade permanente e a fácil abordagem da área doadora.…”
Section: Tecidos Utilizados Na Uretroplastiaunclassified